MANIFESTATIONS OF POSTMODERNISM IN HERMANN HESSE’S NOVEL “THE GLASS BEAD GAME” - Arakelyan, Ara (Armenian Folia Anglistika, 2023)
The paper attempts to consider the connections between postmodernism, aesthetics and Herman Hesse’s novel The Glass Bead Game referring to the history of the last most influential manifestation of the theoretical and aesthetic thought of the West – postmodernism, also characterized by paradoxes. Based on a number of fundamental principles of the aesthetics of postmodernism and data on the work of Hermann Hesse, the specific relations that connect Hesse’s work with postmodernism, are considered. This refers first to the ideas of the world as chaos, then aesthetic eclecticism, multiculturalism and finally game. Within the framework of the idea the world as chaos, the wide use of the concept of simulacrum in both Hesse’s and postmodernist works is considered. Aesthetic eclecticism, which is “the dominant sign of the culture of the postmodern era” (J.-F. Lyotard, I. Ilyin), is also found in Hesse’s novel in various manifestations. Multiculturalism, both as a social utopia and as an aesthetic principle, is also widespread among postmodernist aesthetes (especially L. Fiedler) and in Hesse’s novel. In the novel the East-West political and cultural dialogue also deepens. Finally, the game, being one of the stable European cultural codes, is rediscovered both in Hesse’s novel and in postmodernist aesthetics (U. Eco).